KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN SURAT PENGANTAR DOKUMEN ADMINISTRASI KEPENDUDUKAN PADA KANTOR KELURAHAN NUNU KECAMATAN TATANGA KOTA PALU - Ashad, Fahria (Katalogis, 2017)
This research aims to know the quality of public services in the management of the Document cover letter Administrative Residency in The Office Of Neighborhood Nunu Subdistrict Tatanga, Palu City. By using the theory of (Parasuraman 2001) with 5 indicators to be a benchmark in the study i.e. Tangibles, Reliability, Responsiviness, Assurance, Emphaty.This research Uses Qualitative Research Methods. Informants in this study amounted to 5 persons include: citizens and employees in The Office OfÂ  Neighborhood Nunu, Subdistrict Tatanga, Palu City. Technique used in determining the informant was purposive technique with the techniques of data collection Techniques in the study uses observations (observation), interview and documentation.The results showed the quality of public services in the management of the Document cover letter Administrative Residency in The Office Of Neighborhood Nunu Subdistrict Tatanga, Palu City evidenced by 5 indicators i.e. the Tangibles are not yet well in the value of the facilities and infrastructure that does not yet support officer in the Ministry of population administration document cover letter. As for the from indicator Realibility, Responsivines, Assurance, and Empaty already well underway it caused to the four indicators based on results of research services in the management of the Document cover letter Administrative Residency in The Office Of Neighborhood Nunu Subdistrict Tatanga, Palu City.according with the results in the expected citizens ranging from the speed employees serving the public, responsiveness, friendliness and politeness and attitude of attentionon serving employees so that the four indicators are already well underway.